2019
DOI: 10.24843/eja.2019.v27.i02.p03
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi, Kedisiplinan, dan Kompetensi Terhadap Kinerja Pengawasan

Abstract: This research was conducted at the Regional Inspectorate and the Regional Financial and Revenue Management Agency of Klungkung Regency. The number of samples taken as many as 42 employees, with non-probability sampling method, proposive sampling technique. Data collection is done through surveys and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that organizational culture, discipline, and competence simultaneously had a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
2
0
8
Order By: Relevance
“…Alternative research was carried out by Cardona et al (2014) to test the effect of cultural and economic factors on a particular country that implemented the IFRS discovered that cultural dimension has a significant effect on the decision to implement the International Financial Reporting Standards (IFRS). Similarly, the study carried out by Sari (2013) reported that organizational culture has a significant effect on the efficient application of public sector accounting. The magnitude of this is classified in the medium category.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 85%
See 1 more Smart Citation
“…Alternative research was carried out by Cardona et al (2014) to test the effect of cultural and economic factors on a particular country that implemented the IFRS discovered that cultural dimension has a significant effect on the decision to implement the International Financial Reporting Standards (IFRS). Similarly, the study carried out by Sari (2013) reported that organizational culture has a significant effect on the efficient application of public sector accounting. The magnitude of this is classified in the medium category.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 85%
“…This is evident in its effects on organizational performance, which depends on the integration, consensus of values, and individual commitments to common goals. Based on a research on culture carried out by Sari (2013) found that organizational culture can support the success of the effectiveness of accounting implementation by increasing the integration of adequate financial information by paying more attention to document management systematically in each section, applying a single and more stringent standard to integrate information between divisions, providing more attention in bridging information between divisions. A study conducted by Hashim (2012) on CEOs of companies in Malaysia shows that the quality of financial reporting cannot be separated from the influence of organizational culture where positive and significant results are found between culture and financial reporting quality.…”
Section: Pendahuluanmentioning
confidence: 99%
“…UMKM yang mampu menerapkan budaya organisasi yang baik akan dapat meningkatkan kinerja. Beberapa penelitian sebelumnya dilakukan oleh (Setiawati et al, 2021), (Hoiron et al, 2019 dan (Laforet, 2016) mendapatkan hasil bahwa budaya organisasi berpengaruh positif dan signifikan terhadap kinerja. Penelitian tersebut juga didukung oleh penelitian (Muttaqien & Cahyaningati, 2023), (Oktavia & Fernos, 2023) Penggunaan secara terus menerus mengindikasikan adanya intensitas pemakaian yang disebabkan adanya net benefits atau manfaat dari e-commerce dan sistem informasi tersebut.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini konsisten dengan penelitian yang dilakukan oleh (Setiawati et al, 2021), (Hoiron et al, 2019, serta (Laforet, 2016) yang menyatakan bahwa budaya organisasi berpengaruh positif dan signifikan terhadap kinerja. Penelitian tersebut juga didukung oleh penelitian (Muttaqien & Cahyaningati, 2023), (Oktavia & Fernos, 2023), dan (Ahmad Syauqi & Riyadi, 2023) yang menyatakan bahwa budaya organisasi berpengaruh positif dan signifikan terhadap kinerja.…”
Section: Metode Penelitianunclassified
“…Kinerja UMKM adalah hasil dari pekerjaan yang direalisasikan sepenuhnya dan jika dibandingkan dengan hasil kerja, target, sasaran atau standar yang diprediksi dan disepakati dalam bisnis dengan aset nilai tambah dan pendapatan yang ditentukan oleh undang-undang (Setiawati et al, 2021).…”
Section: Kinerja Usaha Mikro Kecil Dan Menengahunclassified